APLIKASI PENDEKATAN SITUASIONAL DALAM MENENTUKAN GAYA KEPEMIMPINAN EFEKTIF - Victor Imaduddin Ahmad (Al Hikmah: Jurnal Studi Keislaman, 2013)
Leadership is a dynamic process, which differs from one situation to another with a change in leadership, followers and situations, adult literature seems to support the situational approach to the study of leadership. Therefore, most of today's leadership is based on the approach of situational or contingency approachThe results revealed that there was no effective leadership style can be applied in all situations and conditions. He further said that the effectiveness of a leadership style is determined by the accuracy or relevance of its application to the maturity level of subordinate ability to perform the functions and duties (the circumstances), so the subordinate maturity level variables determine the effectiveness of a leadership style.The level of maturity is the ability to subordinate levels of ability and willingness of subordinates in carrying out its functions and duties levied. The ability of subordinates related to the knowledge and skills acquired subordinates from education, training and experience. While the willingness of subordinates related to motivation and morale of subordinates as well as the satisfaction of their work.